Research And Development Of Selfemulsifying Drug Delivery System (SEDDS) For Enhanced Bioavailability Of Curcumin - Chiang, Xin Yen (2019)
The present study was conducted to formulate a sel f-emulsifying (SE) system for enhancing the systemic absorption of poor bioavailable lipophilic curcumin. A simple high performance liquid chromatographic method with the required specificity, precision and accuracy was first developed for quantification of curcumin in rat and human plasma.